Interaction between Mitochondrial Reactive Oxygen Species, Heme Oxygenase, and Nitric Oxide Synthase Stimulates Phagocytosis in Macrophages - Müllebner, Andrea; Dorighello, Gabriel G.; Kozlov, Andrey V.; Duvigneau, J. Catharina (Frontiers in Medicine, 2018)
Background Macrophages are cells of the innate immune system that populate every organ. They are required not only for defense against invading pathogens and tissue repair but also for maintenance of tissue homeostasis and iron homeostasis. Aim The aim of this study is to understand whether heme oxygenase (HO) and nitric oxide synthase (NOS) contribute to the regulation of nicotinamide adenine dinucleotide phosphate oxidase (NOX) activity and phagocytosis, two key components of macrophage function. Methods This study was carried out using resting J774A.1 macrophages treated with hemin or vehicle. Activity of NOS, HO, or NOX was inhibited using specific inhibitors. Reactive oxygen species (ROS) formation was determined by Amplex® red assay, and phagocytosis was measured using fluorescein isothiocyanate-labeled bacteria. In addition, we analyzed the fate of the intracellular heme by using electron spin resonance. Results We show that both enzymes NOS and HO are essential for phagocytic activity of macrophages. NOS does not directly affect phagocytosis, but stimulates NOX activity via nitric oxide-triggered ROS production of mitochondria. Treatment of macrophages with hemin results in intracellular accumulation of ferrous heme and an inhibition of phagocytosis. In contrast to NOS, HO products, including carbon monoxide, neither clearly affect NOX activity nor clearly affect phagocytosis, but phagocytosis is accelerated by HO-mediated degradation of heme. Conclusion Both enzymes contribute to the bactericidal activity of macrophages independently, by controlling different pathways.